Integrating the Patient Perspective into Healthcare and Real-World Evidence: The Multi-site, Cross-Disease, Patient-Centered Outcomes Research Project in the Medical Informatics Initiative (PCOR-MII) - Rogge, A. A.; Mukowski-Kickhöfel, R.; Boeker, M.; Budde, K.; Debertshäuser, T.; Dugas, M.; Erim, Yesim; Friederich, H. C.; Ganslandt, Thomas; Giel, K.; Henningsen, P.; Herrmann, T.; et al. (Journal of Healthcare Informatics Research, 2025)
This paper presents the Patient-Centered Outcomes Research within the Medical Informatics Initiative (PCOR-MII) project, focusing on the integration of patient-reported outcomes (PROs) into a large-scale national data sharing infrastructure, established in Germany by the Medical Informatics Initiative (MII). PCOR-MII aims to systematically address the interests of various stakeholders in patient-reported health data and three dimensions of clinical utility: (1) prediction, (2) monitoring, and (3) outcome assessment. The project builds upon harmonized technical, data, and compliance environments established at the participating institutions as part of the MII to deploy and roll out software solutions for capturing PROs and making them accessible within local electronic health record (EHR) systems. To overcome interoperability challenges, PCOR-MII is developing a construct-oriented PROM module for the Health Level 7 (HL7) Fast Healthcare Interoperability Resources (FHIR)–based German National Core Dataset. The project applies its approach to three patient populations with distinct characteristics: anorexia nervosa targeting risk prediction (dimension 1), kidney transplantation prioritizing health status and adherence monitoring (dimension 2), and persistent somatic symptoms primarily aimed at assessing and understanding outcomes (dimension 3). With their emphasis on different aspects of PROs, those application areas can serve as blueprints for a broader roll-out. PCOR-MII represents a structured and comprehensive effort to incorporate PROs into a national data infrastructure, promising more precise diagnostics, improved treatment decisions, and the generation of new biomedical insights. We believe that our structured approach may serve as a guiding framework for others aiming to implement PROs in diverse healthcare settings.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Chronic disease management; Health data integration; Monitoring treatment; Patient-centered care; Patient-reported outcomes; Real-world evidence